Conflict in the Perspective of Multicultural Education - Siregar, Izuddinsyah; Pramudita, Pramudita (Universitas Tanjungpura, 2025)
Conflict is an inherent phenomenon in social life and a major challenge in multicultural societies. Differences in values, social status, power, and the unequal distribution of resources often serve as the primary triggers of conflict. This study aims to analyze conflict from the perspective of multicultural education and explore the role of education in mitigating social tensions. Through a theoretical literature-based analysis, this study finds that multicultural education plays a strategic role in fostering social awareness and competencies to create harmony in diverse societies. The key findings of this study indicate that conflict in multicultural societies can be explained through various theoretical perspectives. Marx views conflict as a consequence of class inequalities and the unjust distribution of resources, while Gurr emphasizes that dissatisfaction with structural injustice is a primary factor driving conflict. Meanwhile, Collier